The Influencing Factors of Financial Satisfaction by Moderating Financial Literacy - Rachma Agustina; Choirun Nisful Laili; Dwi Ari Pertiwi (Jurnal Economic Resource, 2022)
One of the areas most affected by this pandemic is the financial sector, starting from finance in the macro (world) scope to the micro (family) sphere. The family finance sector is the basic support for the country's economic progress. Micro-scale financial policies are primarily aimed at underprivileged families in the form of direct cash assistance. This study aims to determine the effect of financial distress and domestic debt on financial satisfaction with financial literacy as a moderator. This research was carried out on lecturers and education staff at Hasyim Asy'ari University Tebuireng Jombang, using quantitative methods. Hypothesis testing using PLS-based SEM, with a research sample of 50 respondents. The results of this study state that 1) Financial distress influences financial satisfaction; 2) Domestic debt is not proven to influence financial satisfaction; 3) Financial literacy influences financial satisfaction; 4) The interaction between domestic debt and financial literacy has no effect on financial distress; 5) The interaction between financial distress and financial literacy has no effect on financial satisfaction.